ANALISIS RESPON MAHASISWA TERHADAP MATA KULIAH TERINTEGRASI ISLAMI KEMUHAMMADIYAHAN DAN PENGHAYATAN TERHADAP NILAI AGAMA ISLAM - Connie Chairunnisa (Faktor Jurnal Ilmiah Kependidikan, 2017)
Abstract: The purpose of this research is to knowing response to the students course integrated al Islamic Kemuhammadiyahan and appreciation the values of relegious Islamic in the postgraduate UHAMKA. This research is using qualitative methods analitic descriptive, with research focus the student semester two and three semester with the amount of respondent as much as 60 students from three classes in postgraduate school UHAMKA. The results of research have meaning that: (1) on the basis of the analysis bi plots response student in class Landasan Ilmu Pendidikan  higher compared with class Evaluasi Program Pendidikan and class Manajemen pendidikan; (2) the results of the interview with student in the three classes such more response to a question is the class of Landasan Ilmu Pendidikan and more appreciate values Islamic relegion, in the marked with ahlaqul karimah students.(3) The class of Landasan Ilmu Pendidikan very respond to the organization’s culture postgraduate UHAMKA  the positive nuanced Islamic relegion. Keywords: Response student to courses integrated AIK